2021
DOI: 10.1002/cpt.2240
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Classification of Drug‐Induced Torsade de Pointes Susceptibility Using Cardiac Simulations and Machine Learning

Abstract: Torsade de Pointes (TdP), a rare but lethal ventricular arrhythmia, is a toxic side effect of many drugs. To assess TdP risk, safety regulatory guidelines require quantification of hERG channel block in vitro and QT interval prolongation in vivo for all new therapeutic compounds. Unfortunately, these have proven to be poor predictors of torsadogenic risk, and are likely to have prevented safe compounds from reaching clinical phases. While this has stimulated numerous efforts to define new paradigms for cardiac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
(153 reference statements)
0
25
0
Order By: Relevance
“…These in silico augmented biomarkers showcase improved sensitivity and specificity with respect to the gold standard human ether-à-gogo and QT prolongation guidelines (Passini et al, 2017 ; Li et al, 2019 ). Currently, these in silico arrhythmogenicity biomarkers focus mainly on lower-fidelity isolated cardiac cell models (Lancaster and Sobie, 2016 ; Britton et al, 2017 ; Fogli Iseppe et al, 2021 ) or simplified cable simulations (Polak et al, 2018 ; Romero et al, 2018 ; Yang et al, 2020 ). The underlying motivation for such an approach is the role of cellular early afterdepolarizations and repolarization failures in providing a trigger for the development of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These in silico augmented biomarkers showcase improved sensitivity and specificity with respect to the gold standard human ether-à-gogo and QT prolongation guidelines (Passini et al, 2017 ; Li et al, 2019 ). Currently, these in silico arrhythmogenicity biomarkers focus mainly on lower-fidelity isolated cardiac cell models (Lancaster and Sobie, 2016 ; Britton et al, 2017 ; Fogli Iseppe et al, 2021 ) or simplified cable simulations (Polak et al, 2018 ; Romero et al, 2018 ; Yang et al, 2020 ). The underlying motivation for such an approach is the role of cellular early afterdepolarizations and repolarization failures in providing a trigger for the development of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to take female sex into account as an independent biological variable by developing two sex-specific in silico augmented multiscale arrhythmogenic risk classifiers. To accomplish this, we first extended the multiscale envelope of studying sex-differences in cardiac electrophysiology beyond the cell or tissue level (Yang et al, 2017 ; Fogli Iseppe et al, 2021 ) up to the organ scale. Next, we used the developed framework to delineate male vs. female arrhythmogenic sensitivity to drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other recent examples of promising studies documenting the applicability of machine learning and artificial intelligence include machine learning modeling of free text data and adverse drug reactions coding for automatic identification of adverse drug reactions from unstructured electronic health record data and by integrating machine learning approaches in preclinical cardiotoxicity risk assessment and contributing patient factors analysis. 17,18 Language processing and text mining software tools can support data collection from electronic health records and provide important insights into real-world drug treatment outcomes. 19 CPT's sister journals are also publishing on machine learning, including two articles highlighted in this issue of CPT.…”
Section: Machine Learning As a Novel Methods To Support Therapeutic Drug Management And Precision Dosingmentioning
confidence: 99%
“…In addition, a range of new translational and quantitative tools are now available to underpin new inclusive clinical development strategies 26 . For example, a recent study published in this journal showed how a combination of mechanistic quantitative systems pharmacology modeling and machine learning provided new insights into sex‐specific classification of drug‐induced Torsade de Pointes (TdP) susceptibility 27 . Notably, it was demonstrated that male‐biased predictive models consistently underestimate TdP risk in women, which suggests that current standard preclinical and clinical safety assessment paradigms are inadequate.…”
Section: Figurementioning
confidence: 99%